Water Quality Evaluation of Kromoleo Swamp Tourist Area using Phytoplankton and Periphyton as Bioindicators in the Sumberpucung Sub-District, Malang, Indonesia - Nudia Mella Pratikasari; Endang Arisoesilaningsih; Catur Retnaningdyah (Program Pascasarjana, 2019)
Kromoleo swamp located in Sumberpucung Malang is used as tourism, fishing, agricultural and fisheries area. The aim of this study was to evaluate the water quality in Kromoleo Swamp based on physical, chemical and biological parameters (phytoplankton and periphyton). Water biotic and abiotic factors were taken at upstream, middle 1 (left and right sides), middle 2 (left and right sides), and downstream (left and right sides). Measurements of water chemical and physics quality included temperature, brightness, solar intensity, turbidity, conductivity, pH, DO, nitrate, orthophosphate, and BOD content, as well as determined by phytoplankton and periphyton as bioindicators. TDI index (Trophic Diatom Index) was used to determine trophic status. Meanwhile, %PTV (Pollution Tolerant Value) was used to determine the level of organic pollution. The results of this study indicated the parameters of water temperature, pH, DO, nitrate and conductivity were still in normal levels, while BOD, turbidity, orthophosphate and water brightness reflected high organic matter pollution. Water quality based on the Shannon-Wiener diversity index of phytoplankton and periphyton was classified as clean water (H'=3.3 – 4.3). However, aquatic trophic status based on TDI index value on phytoplankton and periphyton (69.10 – 86.71) were categorized as eutrophic to hyper eutrophic water. While the pollution level based on % PTV in phytoplankton and periphyton ( 27.62 - 66.88%) grouped into lightly - heavy organic polluted.Keywords: Periphyton, Phytoplankton, Swamp, Tourism, Water Quality.